Chronic recurrent urticaria in patient with recurrent herpes labialis: complete remission after administration with Aciclovir and antihistamines - Georgi Tchernev; Simona Kordeva (Dermatology Reports, 2023)
A 41-year-old female presented in the dermatology department with primary complaints, dating for 2 months, of occasionally appearing and disappearing itching rashes over the whole body [...].